Sedative use: its association with harmful alcohol use, harmful tobacco use and quality of life among health care workers in Thailand - Jiraporncharoen W. (2017)
© 2016 Taylor & Francis Group, LLC. Abstract: Background: Health care workers (HCWs) may be at higher risk for sedative misuse due to potential access and self-medication behavior. Objectives: To examine risk factors for harmful sedative use (HSedU) and its association with harmful alcohol use (HAlcU), harmful tobacco use (HTobU) and quality of life (QoL). Methods: A survey was conducted in 2013 at an urban university hospital in Northern Thailand. Risk of harm was measured using The Alcohol, Smoking and Substance Involvement Screening Test (ASSIST). Harmful substance use defined as having at least moderate risk of harm. QoL was measured using SF-36 questionnaire. Results: A sample of 3204 HCWs (59.7% response) participated. The prevalence of HSedU in past 3 months was 4.2%. Health professionals involved with prescribing or dispensing medication were at higher risk of HSedU (OR 1.80, 95% CI 1.21–2.67). Adjusting for confounders, HSedU was associated with HAlcU (OR 3.35, 95% CI 1.81–6.20) bu t not associated with HTobU. HSedU was associated with lower QoL score which was 7.78 and 5.52 points lower for physical (95% CI −10.4 to −5.18) and mental QoL (95% CI −7.11 to −3.93), respectively. Conclusions: HCWs were at higher risk of HSedU. HSedU was associated with HAlcU and associated with lower physical and mental health QoL.